Study on the mechanism of erosion and wear of elbow pipes by coarse particles in filling slurry - Chunming Ai; Zhe Wang; Chao Liu; Aixiang Wu (Scientific Reports)
Abstract Coarse particles in filling slurry are the primary factor causing wear in filling elbow pipes, and the wear mechanism of these particles on the pipes is influenced by various factors. To study the erosion and wear mechanism of elbow pipes caused by coarse particles, the motion state of coarse particles under different curvature radii, coarse particle gradations, and pipe diameters was investigated using a simulation method based on the coupling of Fluent and EDEM software, grounded in theories of fluid mechanics, rheology, and solid–liquid two-phase flow. The study explored the impact patterns and locations of wear induced by coarse particles on filling elbow pipes. The analysis results indicate that increasing the curvature radius leads to more punctate wear at the elbow and upstream wear. Increasing the proportion of finer particles in the coarse particle gradation forms a better cushioning layer and reduces erosion wear. Enlarging the pipe diameter shifts the high-low concentration boundary of coarse particles towards the elbow outlet and reduces erosion wear. The research findings provide significant references for optimizing coarse particle gradation and preventing pipe wear.